Magnetic resonance imaging at ultra-high magnetic field strength: an in vivo assessment of number, size and distribution of pelvic lymph nodes - Fortuin, Ansje S.; Ladd, Mark E. (PLOS ONE, 2020)
Objective: The definition of an in vivo nodal anatomical baseline is crucial for validation of representative lymph node dissections and accompanying pathology reports of pelvic cancers, as well as for assessing a potential therapeutic effect of extended lymph node dissections. Therefore the number, size and distribution of lymph nodes in the pelvis were assessed with high-resolution, large field-of-view, 7 Tesla (T) magnetic resonance imaging (MRI) with frequency-selective excitation. Materials and methods: We used 7 T MRI for homogeneous pelvic imaging in 11 young healthy volunteers. Frequency-selective imaging of water and lipids was performed to detect nodal structures in the pelvis. Number and size of detected nodes was measured and size distribution per region was assessed. An average volunteer-normalized nodal size distribution was determined. Results: In total, 564 lymph nodes were detected in six pelvic regions. Mean number was 51.3 with a wide range of 19-91 lymph nodes per volunteer. Mean diameter was 2.3 mm with a range of 1 to 7 mm. 69% Was 2 mm or smaller. The overall size distribution was very similar to the average volunteer-normalized nodal size distribution. Conclusions: The amount of in vivo visible lymph nodes varies largely between subjects, whereas the normalized size distribution of nodes does not. The presence of many small lymph nodes (≤2mm) renders representative or complete removal of pelvic lymph nodes to be very difficult. 7T MRI may shift the in vivo detection limits of lymph node metastases in the future.